2015
DOI: 10.1097/bor.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-associated amino-peptidase 1 and rheumatic disease

Abstract: Purpose of review This article will review the genetic evidence implicating ERAP1, which encodes the endoplasmic reticulum-associated amino-peptidase 1, in susceptibility to rheumatic disease. Recent findings Genetic variants and haplotypes of ERAP1 are associated with ankylosing spondylitis, psoriasis, and Behçet’s disease in people of varying ancestries. In each of these diseases, disease-associated variants of ERAP1 have been shown to interact with disease-associated class I Human Leukocyte Antigen (HLA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 27 publications
7
115
0
1
Order By: Relevance
“…Several studies agree to indicate the high trimming Met349/Lys528/Asp575/Arg725/Gln730 haplotype as being associated most strongly with AS risk, while the low trimming Val349/Arg528/Asn575/Gln725/Glu730 haplotype as the most protective [2,78,88]. In contrast, a report has suggested that rare hyperactive or hypoactive allotype pair combinations found in AS patients could explain the involvement of ERAP1 in the disease [79].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitismentioning
confidence: 72%
See 3 more Smart Citations
“…Several studies agree to indicate the high trimming Met349/Lys528/Asp575/Arg725/Gln730 haplotype as being associated most strongly with AS risk, while the low trimming Val349/Arg528/Asn575/Gln725/Glu730 haplotype as the most protective [2,78,88]. In contrast, a report has suggested that rare hyperactive or hypoactive allotype pair combinations found in AS patients could explain the involvement of ERAP1 in the disease [79].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitismentioning
confidence: 72%
“…In particular, two of these SNPs, rs30187 (Arg528Lys) and rs27044 (Glu730Gln), reached high statistical significance for AS, as the minor alleles were robustly more frequent in AS patients than controls. Afterwards, several studies replicated these genetic associations, imputed ERAP1 haplotypes and found further associations with other SNPs mapping in the coding, UTR or intronic regions [2,78,87]. In 2011, it was proved that the association of ERAP1 with AS occurred exclusively in HLA-B27-positive patients, pointing at a gene-gene epistatic interaction [5].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitismentioning
confidence: 81%
See 2 more Smart Citations
“…*Haplotype numbers according to Ombrello et al 12. These eight haplotypes represent all the coding haplotypes with frequency >1% in the Turkish controls and account for 98.8% of the haplotypes predicted with probability >0.8.…”
Section: Methodsmentioning
confidence: 99%